A study of profile of meconium aspiration syndrome in relation with birth weight and gestational age of newborns and their immediate outcome - Uniyal, Preeti; Kalra, B. P.; Wasim, Sanober (International Journal of Contemporary Pediatrics, 2021)
Background: Meconium aspiration syndrome (MAS) is one of the common causes of neonatal respiratory distress. Overall frequency of meconium stained amniotic fluid (MSAF) ranges between 5 to 25%. Methods: Observational study was conducted on 96 newborns over a period of one year in the department of pediatrics, Himalayan Institute of Medical Sciences, Dehradun, Uttarakhand. All newborns, inborns and outborns with MSAF admitted in NICU of our hospital were taken. Results: Out of 876 babies those had MSAF, 96 babies developed MAS with 10.95% incidence. Common maternal risk factors noted with MAS was maternal diabetes mellitus in 11 (15.71%) cases. Babies born via LSCS developed MAS in 51 (53.12%) and in babies delivered vaginally 45 (46.87%). MAS occurred mainly in term with mean gestational age of 38 weeks with SD of 1.85 weeks. The mean birth weight of newborns with MAS was 2794 g with 524 g SD. Most common complication was birth asphyxia in 36 (37.5%). Mortality occurred in 11 (11.4%). Mean gestational age and birth weight of mortality in MAS was 38 weeks with 2.5 weeks SD and 2800 g with 723 g SD respectively. Statistically significant association noted between mortality due to MAS and birth weight as p value<0.05, but no significant association noted between mortality and gestational age. Conclusions: MAS is a common cause of respiratory distress in newborns born through MSAF. With judicious use of available modes of ventilation and adjunctive therapies, infants with even the most severe MAS can usually be supported through the disease, with an acceptable burden of short-and long-term morbidity.